A Novel Method for Prediction of Propellant Shelf‐Life Based on Arrhenius Equation. Issue 4 (30th March 2018) - Zhao, Xin; Rui, Xiaoting; Wang, Yan; Zhang, Ruihua
Abstract: The content of diphenylamine (DPA) greatly influences the storage life of a single‐base propellant. According to the aging test, a novel method for establishing the reaction kinetic model based on Arrhenius equation is proposed to describe DPA depletion. The model deduced not only exactly describes the DPA depletion in the test, but also accurately estimates the DPA content at 55 °C, which gives a prediction of the propellant shelf‐life. This research develops a novel model for the reaction kinetic of DPA, and lays a theoretical foundation for the prediction of a propellant shelf‐life. Abstract :